A Review of Low-Cost Natural Adsorbents for Heavy Metal Removal from Wastewater - Singh, Kulbir (Journal of Research in Science and Engineering, 2026)
Heavy metal contamination in wastewater, stemming from industrial activities like mining and manufacturing, poses significant environmental and health risks due to the persistence and toxicity of metals such as lead, cadmium, and nickel. This review evaluates the efficacy of low - cost, natural adsorbents—such as eggshells, rice husks, and tea waste in removing these pollutants from industrial effluents. While conventional methods like chemical precipitation and electro dialysis are effective, their high costs and sludge generation limit widespread use. This study synthesizes findings on adsorption as a simple, eco - friendly alternative, detailing the performance of various biomaterials and their potential to address a pressing global challenge.